Manajemen Keuangan Bagi Kelompok Pembatik Ecoprint Berbasis Digital Marketing – Purbalingga - Cahyo Budi Santoso; Giovanny Bangun Kristianto; Dianningsih Dianningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This Community Service (PKM) aims to improve financial management and digital marketing skills for ecoprint batik groups in Purbalingga. This program is motivated by the needs of craftsmen to develop local economic potential by improving skills in managing finances and utilizing digital technology for product marketing. Through a participatory approach and intensive training, this PKM activity provides an in-depth understanding of good financial management and effective digital marketing strategies. The results of this program show a significant increase in the financial management skills and digital marketing skills of the participants. Thus, this PKM has succeeded in empowering ecoprint batik groups to be more financially independent and able to compete in a wider market through optimizing digital marketing.